Quantitative histological and histochemical studies of different muscles of the lower limb in diabetes mellitus cases - W. S. , Wan Muhammad Salahudin; Tun, Ye; Zulkifly, Ahmad Hafiz (2011)
Diabetes mellitus causes several changes in fiber size and oxidative capacity in skeletal muscle. Gastrocnemius, Soleus and Anterior Tibialis muscle are important leg muscles involve in reconstruction of amputation stump. The fiber size and oxidative enzyme are important factors related to the viability of muscle and subsequently stump healing. Aim of the study: To describe the fiber size and oxidative capacity quantitatively in 3 muscles of the leg Materials and methods: Specimen obtained from the 10 diabetes mellitus subjects undergone below knee amputation (BKA). Specimen was stained for enzyme histochemistry NADH-TR staining. The slide was analyzed with ImageJ software for fiber type distribution and oxidative capacity based on staining density. Result and discussion: Gastrocnemius muscle has predominantly Type 1 muscle fibers and highest oxidative capacity, while the anterior tibialis muscle has predominantly Type 2 muscle fibers and lowest oxidative capacity. Soleus muscle has almost equal Type 1 and 2 muscle fibers and has intermediate oxidative capacity. Conclusion: Muscle with predominant type 1 fibers has highest oxidative capacity.